Ensino da língua portuguesa para surdos: o SignWriting como sistema de escrita na aprendizagem de uma segunda língua - Alves, Kledson de Albuquerque (2024)
Sign Languages (SL) form the way of linguistic expression for deaf people. To record the signs that make up these languages, a specific writing system was created, internationally known as SignWriting (SW). This system allows the recording of LS parameters: hand configurations, locations, movements, hand orientations and facial expressions. Thinking about learning the Portuguese language for deaf students through SW, our research investigates the application of this Libras writing system for students at the Escola Estadual de Audiocomunicação Demóstenes Cunha Lima – EDAC, in Campina Grande – PB, for 4th year students and 5th year of Elementary School. To theoretically substantiate this work, I relied on some authors such as Vygotsky (1993), Quadros (2000), Dallan and Mascia (2012) among others. As for the methodology, research will be carried out with a qualitative, exploratory approach, based on Gil (2002) and Darlan (2009). Considering, from this perspective, that deaf students do not have mastery of SW as a pedagogical practice for learning a second language (L2), we ask ourselves: how can SW help deaf students in learning Portuguese? This analysis will help us to systematize linguistic and methodological knowledge from a SW teaching experience, aimed at improving the performance of deaf students in writing in the L2. The investigative interest is based on conceptssuch as acquisition ofsign and writtenLibras, bilingualism, sign language writing and interlanguage – such as writing in L2. Based on this research, we will produce video classes with didactic-pedagogical guidelines for teachers who teach in a Bilingual School for the deaf, with the aim of contributing to the mediation of learning regarding SignWriting.